Artificial Intelligence Adoption and Teacher Performance: The Role of Leadership and Motivation in School Management - Hartini Haritani; Hary Murcahyanto (Universitas Nurul Jadid, 2025)
The rapid integration of digital technology in education has created new opportunities for improving teaching effectiveness and teacher performance. However, the successful implementation of technological innovation in education is influenced not only by technology adoption but also by organizational and motivational factors within schools. This study aims to analyze the influence of AI technology, principal leadership, and teacher motivation on teacher performance in East Lombok. This research employed a quantitative approach using multiple linear regression analysis to examine the relationships between the independent variables and teacher performance. Data were collected through questionnaires distributed to nine teachers selected through purposive sampling. The results indicate that AI technology has a significant positive influence on teacher performance with a regression coefficient of 0.588 and a significance value of 0.035. Meanwhile, principal leadership and teacher motivation show negative regression coefficients of −0.165 and −0.003 respectively, although their statistical influence remains significant. The regression model explains 84.2% of the variation in teacher performance, indicating a strong relationship between the variables examined in this study. These findings highlight the importance of integrating technological innovation with effective educational management strategies in order to improve teacher performance. The study suggests that educational institutions should strengthen the utilization of AI-based technologies while promoting leadership practices and motivational strategies that support teachers in adapting to digital transformation in education.